(untitled) (Research, Society and Development, 2021)
The aim of this study was to identify scientific evidence about good practices in newborn care, from the delivery room to the home, in times of COVID-19. This is an Integrative review. Thus, the design of this study arose from the following research question: what is known so far in the scientific literature on newborn care practices, in times of pandemic? After going through the methodological steps, it was possible to identify 06 articles, all publications are dated in 2020 and focused on prevention and care provided to newborns. In view of the analysis of the available literature, there were several differences on the implementation of care practices. In view of this, it is feasible to create a protocol to assist newborns in times of pandemic of COVID-19, in order to establish a quality standard. Still, more research is needed regarding assistance to newborns considering the COVID-19 pandemic period, especially of Brazilian authors.